Cerebral small vessel disease in middle age and genetic predisposition to late‐onset Alzheimer's disease. Issue 2 (20th November 2017) - Stefaniak, James D.; Su, Li; Mak, Elijah; Sheikh‐Bahaei, Nasim; Wells, Katie; Ritchie, Karen; Waldman, Adam; Ritchie, Craig W.; O'Brien, John T.
Abstract: Introduction: Cerebral small vessel disease (CSVD) is associated with late‐onset Alzheimer's disease (LOAD) and might contribute to the relationship between apolipoprotein E ε4 ( APOE ε4) and LOAD, in older people. However, it is unclear whether CSVD begins in middle age in individuals genetically predisposed to LOAD. Methods: We assessed the relationship between radiological markers of CSVD, white matter hyperintensities and microbleeds, and genetic predisposition to LOAD in a cross‐sectional analysis of cognitively normal subjects aged 40–59 years recruited from the PREVENT Dementia study. Results: Microbleed prevalence was 14.5%, and mean ± standard deviation white matter hyperintensity percentage of total brain volume was 0.41 ± 0.28%. There was no significant association between APOE ε4 carrier status or history of parental dementia and white matter hyperintensity volume ( P  = .713, .912 respectively) or microbleeds ( P  = .082, .562 respectively) on multiple regression. Discussion: Genetic predisposition to LOAD, through APOE genotype or AD family history, is not associated with CSVD in middle age. Highlights: Cerebral small vessel disease was assessed in middle‐aged subjects. Cerebral microbleed prevalence was 14.5%. Cerebral small vessel disease was not associated with APOE or parental history of Alzheimer's disease.